Recovery of Nutrients from Residual Streams Using Ion-Exchange Membranes: Current State, Bottlenecks, Fundamentals and Innovations - Natalia Pismenskaya; Kseniia Tsygurina; Victor Nikonenko (Membranes, 2022)
The review describes the place of membrane methods in solving the problem of the recovery and re-use of biogenic elements (nutrients), primarily trivalent nitrogen NIII and pentavalent phosphorus PV, to provide the sustainable development of mankind. Methods for the recovery of NH4+ − NH3 and phosphates from natural sources and waste products of humans and animals, as well as industrial streams, are classified. Particular attention is paid to the possibilities of using membrane processes for the transition to a circular economy in the field of nutrients. The possibilities of different methods, already developed or under development, are evaluated, primarily those that use ion-exchange membranes. Electromembrane methods take a special place including capacitive deionization and electrodialysis applied for recovery, separation, concentration, and reagent-free pH shift of solutions. This review is distinguished by the fact that it summarizes not only the successes, but also the “bottlenecks” of ion-exchange membrane-based processes. Modern views on the mechanisms of NH4+ − NH3 and phosphate transport in ion-exchange membranes in the presence and in the absence of an electric field are discussed. The innovations to enhance the performance of electromembrane separation processes for phosphate and ammonium recovery are considered.